General practice critical incident reviews of patient suicides: benefits, barriers, costs, and family participation. Issue 1 (3rd February 2005) - King, E; Kendall, K; Wiles, R; Rosenvinge, H; Gould, C; Kendrick, A
Abstract : Aim: To explore the feasibility of holding critical incident reviews (CIRs) after patient suicides in general practice and their ability to change practice. Methods: Thirteen practices were invited to conduct a facilitated CIR on 18 current patient suicides. Next of kin views were sought. All staff attending a CIR were interviewed after the review. Results: Ten practices reviewed 12 deaths. Twenty six staff attended reviews; all were interviewed. Next of kin contributed to six reviews; only one criticised care. Changes following the reviews included steps to improve internal communication and bereavement support to set up internal CIRs and review prescribing policies. Communications between practices and other agencies were clarified. Conclusion: Practices were willing to hold CIRs and appreciated the potential positive value but need reassurance that they will not be blamed for suicides, and that the cost in time and resources will be recognised.